2020
DOI: 10.1007/s11573-020-00991-1
|View full text |Cite
|
Sign up to set email alerts
|

Tensions in sustainable warehousing: including the blue-collar perspective on automation and ergonomic workplace design

Abstract: In many industrial countries, demographic changes towards an aging society go hand in hand with the need for ergonomic workplaces. Therefore, it is necessary to rethink workplace designs and work processes, particularly in industrial professions, such as logistics. As logistics activities are still characterized by a high amount of manual effort, they represent a suitable field for gaining empirical insights into the implementation of automation and ergonomic practices to inform social sustainable warehousing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…By investigating tensions on individual, organizational and supply chain levels, Gruchmann et al (2020) were able to explain why automation and ergonomic practices in warehouse logistics are not adequately implemented, despite health, safety and operational performance benefits. They found that tensions are primarily caused by increased cognitive requirements for these workplace innovations versus supply chain customer pressures based on price and flexibility.…”
Section: Unanticipated Outcomes In the Quest For Sustainabilitymentioning
confidence: 99%
“…By investigating tensions on individual, organizational and supply chain levels, Gruchmann et al (2020) were able to explain why automation and ergonomic practices in warehouse logistics are not adequately implemented, despite health, safety and operational performance benefits. They found that tensions are primarily caused by increased cognitive requirements for these workplace innovations versus supply chain customer pressures based on price and flexibility.…”
Section: Unanticipated Outcomes In the Quest For Sustainabilitymentioning
confidence: 99%
“…A detailed discussion is hereinafter provided for each factor identified: Costs: although several authors agree that embracing greener warehouse operations helps protect the environment ethically and comply with the reduction of operational costs in the long run (Salhieh and Abushaikha, 2016; Minashkina and Happonen, 2020), there is still a mental bias that brings logistics operators thinking that environmental sustainability is just a source of additional costs rather than a strategic opportunity for differentiating their businesses (Goh, 2019). According to the survey by Kaur and Awasthi (2018), besides investment costs, managers are scared by the potential costs of environmentally friendly packaging, hazardous waste disposal and the expenses of switching to new systems. Complexity: the literature suggests that the introduction of sustainability initiatives may add levels of complexity in organisations (Goh, 2019; Gruchmann et al ., 2021). Implementation can be challenging and sustainable practices need time and effort to be diffused within a company and amongst all supply chain players that have to adapt to sustainable standards or performance criteria. Communication: insufficient or missing communication is a typical barrier (Kaur and Awasthi, 2018; Goh, 2019; Gruchmann et al ., 2021).…”
Section: Results and Framework Developmentmentioning
confidence: 99%
“…According to the survey by Kaur and Awasthi (2018), besides investment costs, managers are scared by the potential costs of environmentally friendly packaging, hazardous waste disposal and the expenses of switching to new systems. Complexity: the literature suggests that the introduction of sustainability initiatives may add levels of complexity in organisations (Goh, 2019; Gruchmann et al ., 2021). Implementation can be challenging and sustainable practices need time and effort to be diffused within a company and amongst all supply chain players that have to adapt to sustainable standards or performance criteria. Communication: insufficient or missing communication is a typical barrier (Kaur and Awasthi, 2018; Goh, 2019; Gruchmann et al ., 2021). In this sense, meetings and consultations amongst employees seem to be critical drivers for receiving feedback and preventing whatever form of resistance (Seuring and Müller, 2008).…”
Section: Results and Framework Developmentmentioning
confidence: 99%
“…On average, between 9-47% of American jobs are estimated to be at risk of automation [2], [18], but this number is significantly higher for lower status blue-collar jobs than higher status white-collar jobs [19], [20]. Many papers have built on these estimates to suggest that blue-collar workers feel significantly more threat from automation than whitecollar workers [21].…”
Section: B Job Status May Moderate the Relationship Between Automatio...mentioning
confidence: 99%